Histologic research on oviducts of cows with symptom free sterility - ΣΕΪΤΑΡΙΔΗΣ, Κ.; ΤΣΑΓΤΑΡΗΣ, Θ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The oviducts of 50 cows with symptom free sterility were examined. One of these cows (2%) showed bilateral hydrosalpingitis. An histologic examination made on the oviducts of the remaining 39 cows showed that 12 cows (24,5%) have had salpingitis and more specially 4 cows (33,3%) on the right oviduct, 3 (25,0%) on the left and 5 (41,7%) on both oviducts. 5 (71,4%) out of 7 cows with unilateral salpingitis showed inflamation lesions in the ampulla and 2 (28,6%) in the isthmus of right or left oviduct, while 2 (40,0%) out of 5 cows with bilateral salpingitis showed these lesions in the ampulla and the isthmus, 1 (20,0%) in the ampulla and 2 (40,0%) in the isthmus of right and left oviduct.